PROJEKT ZMIANY KONSTYTUCJI RP PRZYGOTOWANY PRZEZ RADĘ PROGRAMOWĄ KONWERSATORIUM „DOŚWIADCZENIE I PRZYSZŁOŚĆ" - Zoll, Andrzej (Wydział Prawa i Administracji UAM, 2009)
The proposal of amendments to the Constitution of the Republic of Poland presented in the paper was initiated by former Presidents Chairmen) of Poland’s Constitutinal Court (Trybunał Konstytucyjny) and subsequently drafted by the Programme Council Seminar „Doświadczenie i Przyszłość”. The proposal is a wholly civic project. It aims to eliminate the tension between two organs holding executive power: president and government. It postulates an amendment to the Constitution that would define presidential office as the highest representative of the Republic and one with guaranteed continuity. At the same the drafters of the amendments propose that the executive power should be exclusively held by the government. Further, they propose to limit presidential veto and consider a possibility of the Seym obliging president to ratify or denounce international treaties. Another variant considers departure from presidential elections.
PROPOSAL OF AMENDMENTS TO THE CONSTITUTION OF THE REPUBLIC OF POLAND